Design, Synthesis In Vitro Anticancer Activity and Docking Studies of (−)‐Catechin Derivatives. (28th January 2015) - Kumar, Deepak; Harshavardhan, S. J.; Chirumarry, Sridhar; Poornachandra, Y.; Jang, Kiwan; Ganesh Kumar, C.; Yoon, Yong‐Jin; Zhao, Bao‐Xiang; Miao, Jun‐Ying; Shin, Dong‐Soo
<x xml:space="preserve">Abstract</x> Novel series of ()‐catechin derivatives 1a‐l were synthesized, characterized and assayed for their cytotoxicity against four selected human cancer cell lines by standard MTT assay method. Most of the compounds significantly active among which 1d exhibited promising activity with IC50 values of 2.5, 4.8 and 5.4 μM specifically against hepatocellular liver carcinoma (HepG2), lung adenocarcinoma (A549) and prostate (DU‐145) cell lines, while compound 1j showed promising cytotoxicity against human breast adenocarcinoma MDA‐MB‐231 (IC50 value of 6.6 μM). Compounds 1a, 1d, 1e, 1f and 1j exhibited broad spectrum cytotoxicity against all the cell lines screened. Molecular docking studies of compound 1d established the good binding affinity and are in favor of the observed biological activity. These data collectively suggest that compound 1d could serve as a new template for further optimization as anticancer agent.